Performance of ISA Brown commercial layer after forced molting (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
A total of 29460 ISA Brown commercial layers were force molted with feed restricted (20g to 70g) forced molting method to assess the effects of molting of ISA Brown commercial layers at Valuka Layer Farm-1, C.P. Bangladesh Co., Ltd. Layers were forced molted between 73 to 76 weeks of age. Forced molting made significant differences on egg production. Egg production (77.11%) and egg weight (66.93g) were increased in post molting period than that in pre molting (67.26%) and molting (22.27%) period. The value of egg weight in pre molting period was 65.51g and molting period was 58.25g. During molting period body weight loss was 193.75g. Whereas, in pre molting and after molting period body weight gain were11.25g and 11.00g respectively. Feed conversion (FC) was significant at 1% level of significance (P